2020
DOI: 10.3233/jad-191040
|View full text |Cite
|
Sign up to set email alerts
|

Effect Modifiers of TDP-43-Associated Hippocampal Atrophy Rates in Patients with Alzheimer’s Disease Neuropathological Changes

Abstract: Background: Transactive response DNA-binding protein of 43 kDa (TDP-43) is associated with hippocampal atrophy in Alzheimer's disease (AD), but whether the association is modified by other factors is unknown. Objective: To evaluate whether the associations between TDP-43 and hippocampal volume and atrophy rate are affected by age, gender, apolipoprotein E (APOE) 4, Lewy bodies (LBs), amyloid-␤ (A␤), or Braak neurofibrillary tangle (NFT) stage. Methods: In this longitudinal neuroimaging-clinicopathological stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 78 publications
8
17
4
Order By: Relevance
“…Given that pathologically only LATE-NC status differed between the two cohorts, this may suggest that additional LATE-NC may have an additive detrimental effect on cognitive impairment that is independent of tau pathology. This finding is in agreement with previous longitudinal clinicopathological studies that determined that TDP-43 pathology is associated with cognitive impairment independent of AD pathology and hippocampal sclerosis [53], and the clinical impact of TDP-43 and tau pathology is statistically independent [28] with their clinical effects exhibited at different time points in the disease progression [19]. On the other hand, cognitive decline was not significantly different between the AD/LATE-NC and AD groups indicating the rate of cognitive decline was not accelerated due to the presence of LATE-NC in contrast to a previous clinicopathological study [10].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Given that pathologically only LATE-NC status differed between the two cohorts, this may suggest that additional LATE-NC may have an additive detrimental effect on cognitive impairment that is independent of tau pathology. This finding is in agreement with previous longitudinal clinicopathological studies that determined that TDP-43 pathology is associated with cognitive impairment independent of AD pathology and hippocampal sclerosis [53], and the clinical impact of TDP-43 and tau pathology is statistically independent [28] with their clinical effects exhibited at different time points in the disease progression [19]. On the other hand, cognitive decline was not significantly different between the AD/LATE-NC and AD groups indicating the rate of cognitive decline was not accelerated due to the presence of LATE-NC in contrast to a previous clinicopathological study [10].…”
Section: Discussionsupporting
confidence: 93%
“…Since all of our cases in this study were neuropathologically confirmed AD cases with a Braak stage V/VI, we did not employ this criterion as virtually all of our cases would be classified as type-b. However, TDP type-b was not found to be associated with the robust neuropathological and genetic correlates of AD, such as CERAD neuritic plaques or APOE e4 genotype, which one may expect if TDP-43 and tau are pathologically linked [28]. Therefore, indicating the higher prevalence of type-b inclusions in AD is perhaps reflective of the simultaneous presence of more severe NFT burden.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations